MATHEMATICS CONTENT AND TECHNICAL AND VOCATIONAL EDUCATION TRAINING: A SYSTEMATIC REVIEW: ВИВЧЕННЯ ЗМІСТУ МАТЕМАТИКИ В КОНТЕКСТІ ПРОФЕСІЙНО-ТЕХНІЧНОЇ ОСВІТИ: СИСТЕМАТИЧНИЙ ОГЛЯД - Acheampong, Philip; Awuah, Francis Kwadwo (Physical and Mathematical Education, 2025)
Formulation of the problem. Mathematics is fundamental to Technical and Vocational Education and Training (TVET). This is because mathematics enables TVET students to develop the problem-solving skills required in their respective trade areas. Despite this, there is ample evidence that TVET students around the world have poor mathematical skills. To address this issue, various studies have focused on TVET students’ performance and interest, teaching mathematics in vocational education, and the relevance of mathematics, with little emphasis on the study of mathematics content in vocational education. This current study presents a systematic analysis of mathematics content in vocational education from January 2015 to January 2024. Materials and methods. Data were collected by analyzing 17 articles on mathematics in TVET from Google Scholar general search, Scopus, the Eric journal, and the EBSCOHost database. The numerical data were presented as percentages and frequencies, whereas the qualitative data were analysed thematically. Results. The study found that the majority of articles were published in 2022, followed by 2017 and 2021. However, the fewest number of articles were published in 2015, 2018, and 2020. The findings also revealed that the majority of authors are affiliated with South Africa, followed by Sweden and Indonesia, with Turkey and Qatar having the fewest affiliations. Finally, the findings revealed that the authors focused on two major themes: teaching mathematics in the context of TVET and the importance of mathematics in TVET. Conclusions. This review emphasizes the importance of additional research in this area to improve the quality of mathematics education in TVET programs around the world in order to meet the workforce’s changing needs.